Survival rates in the world's southernmost forest bird community - Sandvig, Erik M.; Quilodrán, Claudio S.; Altamirano, Tomás A.; Aguirre, Francisco; Barroso, Omar; Rivero de Aguilar, Juan; Schaub, Michael; Kéry, Marc; Vásquez, Rodrigo A.; Rozzi, Ricardo (Ecology and Evolution, 2023)
Article asserts that the Magellanic sub-Antarctic Forest is home to the world's southernmost avian community and is the only Southern Hemisphere analogue to Northern Hemisphere temperate forests at this latitude. Authors describe annual survival patterns and their association with climate variables using a 20-year mark–recapture data set of five forest bird species in the Cape Horn Biosphere Reserve.